Report on consumer acceptability tests of NARITA hybrids in Tanzania and Uganda - Marimo, Pricilla; Nowakunda, K.; Aryamanya, W.; Azath, H.; Babley, H.F.; Kazigye, F.; Khakasa, E.; Kibooga, C.; Kibura, J.K.; Kindimba, Grace; Kubiriba, Jerome; Magohe, R.B.; et al. (2020)
Consumer acceptability tests of NARITA hybrids were conducted with a total of 572 randomly selected men and women farmers from 5 sites in different agro-ecological zones in Tanzania and Uganda (Maruku, Mitalula and Moshi in Tanzania; Kawanda and Mbarara in Uganda). Evaluations were done between July and November 2018 under the project ‘Improvement of banana for smallholder farmers in the Great Lakes Region of Africa’. At each site, focus group discussions (FGDs) were first conducted with different age groups: young women, young men (<35 years); and older women, older men (>35 years) to ascertain the main products households make using cooking banana cultivars and the preparation method. The most important product was then prepared in each site - steamed matooke in both Uganda sites and boiled fingers in all Tanzania sites. On a given day, about 100 farmers were each provided with coded samples of four NARITA hybrids plus one local check and asked to rate each sample on a 5-point hedonic scale for the following attributes: colour, aroma, texture in hand, taste, mouthfeel and overall acceptability. This report provides results that can help inform the selection of the best NARITAs to take on-farm and subsequent varietal release.